2017
DOI: 10.1038/nrd.2017.221
|View full text |Cite
|
Sign up to set email alerts
|

Drug development for neurodevelopmental disorders: lessons learned from fragile X syndrome

Abstract: Neurodevelopmental disorders such as fragile X syndrome (FXS) result in lifelong cognitive and behavioural deficits and represent a major public health burden. FXS is the most frequent monogenic form of intellectual disability and autism, and the underlying pathophysiology linked to its causal gene, FMR1, has been the focus of intense research. Key alterations in synaptic function thought to underlie this neurodevelopmental disorder have been characterized and rescued in animal models of FXS using genetic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
274
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(279 citation statements)
references
References 133 publications
2
274
0
1
Order By: Relevance
“…For example, in the case of Fragile X syndrome, an abnormal expansion of the CGG triplet repeats on the chromosome X gene for the FMR1 protein causes silencing of the gene and lack of the protein, thus ultimately resulting in dysregulation of the balance between the glutamatergic excitatory neurotransmission and the GABAergic inhibitory one 57. Building on this knowledge, pharmacological approaches have recently been tested in an attempt to correct the neurotransmission imbalance and thus improve the associated behavioural symptoms 58. Even though this line of research is in progress and has not produced effective treatments as yet, it signals a new approach to drug development in child psychopharmacology.…”
Section: Unmet Needsmentioning
confidence: 99%
“…For example, in the case of Fragile X syndrome, an abnormal expansion of the CGG triplet repeats on the chromosome X gene for the FMR1 protein causes silencing of the gene and lack of the protein, thus ultimately resulting in dysregulation of the balance between the glutamatergic excitatory neurotransmission and the GABAergic inhibitory one 57. Building on this knowledge, pharmacological approaches have recently been tested in an attempt to correct the neurotransmission imbalance and thus improve the associated behavioural symptoms 58. Even though this line of research is in progress and has not produced effective treatments as yet, it signals a new approach to drug development in child psychopharmacology.…”
Section: Unmet Needsmentioning
confidence: 99%
“…Inhibition of mGluR5, either through genetic or pharmacological intervention, rescues both cellular and behavioral alterations in animal models of Fmr1 mutation, and consequently mGluR5 inhibitors have been developed for clinical testing. 5 Several clinical trials have tested the efficacy of two different mGluR5 antagonists, mavoglurant and basimglurant, at ameliorating the symptoms associated with FXS. An early-phase trial demonstrated efficacy measured using the Aberrant Behavior Checklist in a post hoc analysis of patients with complete silencing of the FMR1 gene (NCT00718341).…”
Section: Fragile X Syndromementioning
confidence: 99%
“…4 FXS, attributable to silencing of FMR1, reduces expression of fragile X mental retardation protein, a protein that affects multiple aspects of RNA metabolism and translation. 5 Disruption of these processes within the brain results in synaptic impairment and alterations in neuronal connectivity that are thought to underlie neurocognitive manifestations, including autism, intellectual disability, and mood disorders, often comorbid with these disorders. The identification of common mechanisms, preclinically linked to behavioral phenotypes, empowers directed target identification for treatment of this symptomatic domain.…”
mentioning
confidence: 99%
“…Once evaluating potentially efficacious interventions, decades of work in pharmacological treatment trials have highlighted the major limitations in many of the most commonly used behavioural measures, which fail to detect important subtle changes that may become even more clinically meaningful in the longer term (Berry‐Kravis et al . ). The speakers at this year's conference remind us of the importance of precision by offering numerous examples of how careful behavioural phenotyping is providing new insights into pathways from gene to behaviour.…”
mentioning
confidence: 97%